From non-obese diabetic to Network for the Pancreatic Organ Donor with Diabetes: New heights in type 1 diabetes research - Ramirez, Lourdes (World J Diabetes, 2015)
Since the discovery of therapeutic insulin in 1922 and the development of the non-obese diabetic spontaneous mouse model in 1980, the establishment of Network for the Pancreatic Organ Donor with Diabetes (nPOD) in 2007 is arguably the most important milestone step in advancing type 1 diabetes (T1D) research. In this perspective, we briefly describe how nPOD is transforming T1D research via procuring and coordinating analysis of disease pathogenesis directly in human organs donated by deceased diabetic and control subjects. The successful precedent set up by nPOD is likely to spread far beyond the confines of research in T1D to revolutionize biomedical research of other disease using high quality procured human cells and tissues.